Regulation of Th1 T Cell Differentiation by Iron via Upregulation of T Cell Immunoglobulin and Mucin Containing Protein-3 (TIM-3) - Pfeifhofer-Obermair, Christa; Tymoszuk, Piotr; Nairz, Manfred; Schroll, Andrea; Klais, Gloria; Demetz, Egon; Engl, Sabine; Brigo, Natascha; Weiss, Günter (Frontiers in Immunology, 2021)
Iron plays an important role in host-pathogen interactions, in being an essential element for both pathogen and host metabolism, but also by impacting immune cell differentiation and anti-microbial effector pathways. Iron has been implicated to affect the differentiation of T lymphocytes during inflammation, however, so far the underlying mechanism remained elusive. In order to study the role of iron in T cell differentiation we here investigated how dietary iron supplementation affects T cell function and outcome in a model of chronic infection with the intracellular bacterium Salmonella enterica serovar typhimurium (S. Typhimurium). Iron loading prior to infection fostered bacterial burden and, unexpectedly, reduced differentiation of CD4+ T helper cells type 1 (Th1) and expression of interferon-gamma (IFN, a key cytokine to control infections with intracellular pathogens. This effect could be traced back to iron-mediated induction of the negative immune checkpoint regulator T cell immunoglobulin and mucin domain-containing protein 3 (TIM-3), expressed on the surface of this T cell subset. In vitro experiments demonstrated that iron supplementation specifically upregulated mRNA and protein expression of TIM-3 in naïve Th cells in a dose-depdendent manner and hindered priming of those T cells towards Th1 differentiation. Importantly, administration of TIM-3 blocking antibodies to iron-loaded mice infected with S. Typhimurium virtually restored Th1 cell differentiation and significantly improved bacterial control. Our data uncover a novel mechanism by which iron modulates CD4+ cell differentiation and functionality and hence impacts infection control with intracellular pathogens. Specifically, iron inhibits the differentiation of naive CD4+ T cells to protective IFN producing Th1 lymphocytes via stimulation of TIM-3 expression. Finally, TIM-3 may serve as a novel drug target for the treatment of chronic infections with intracellular pathogens, specifically in iron loading diseases.